Rekonstruksi Penyelesaian Sengketa Konsumen Melalui Penguatan Kelembagaan Perlindungan Konsumen sebagai Perwujudan Bela Negara - Rio Priambodo; Siti Rifqa Raihani; Slamet Tri Wahyudi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Law Number 8 of 1999 on Consumer Protection constitutes an important legal foundation for safeguarding consumer rights in Indonesia. However, in practice, the implementation of consumer protection still faces various challenges, particularly related to institutional weaknesses in handling consumer dispute resolution. This study aims to identify the weaknesses of consumer protection institutions, namely the National Consumer Protection Agency (BPKN), the Consumer Dispute Resolution Body (BPSK), and Non-Governmental Consumer Protection Organizations (LPKSM), in effectively exercising their functions and authorities. Several issues identified include limited resources, weak institutional authority, low public awareness of consumer rights, and insufficient coordination among relevant institutions. Furthermore, this research proposes strategies for strengthening consumer protection institutions in the future through structural reform, enhancement of human resource capacity, and optimization of digital-based dispute resolution systems that are faster, more affordable, and fair. Such strengthening not only improves the effectiveness of dispute resolution but also represents a tangible form of state defense in the context of protecting citizens’ rights as consumers in achieving the Sustainable Development Goals (SDGs). Thus, the state actively plays a role in ensuring justice and legal certainty in national economic activities.